Land Management for Reducing Bank Erosion: Using AHP Method and GIS Technique: A Case Study in Dibru River Basin, Assam India - Sonowal, Gulap; Thakuriah, Gitika (Geological Agency, 2025)
The site suitability for land management in reducing bank erosion is an important step towards sustainable development by adopting conservative measures. Land is considered to be very crucial for maintaining an ecosystem which is helpful to sustaining all forms of life. The increasing bank erosion day to day has been one of the common issues in Assam. The present study aim is to identify the sensitive areas of the bank erosion within the Dibru River Basin. Multicriterion calculation was carried out using geographic information system (GIS) technique to help the choice makers in identifying the fit sites of bank erosion. Different parameters which were considered for multicriterion evaluation, ie. landuse-landcover, geomorphology, soil capability, soil texture, slope, and river distances were taken for identifying the vulnerable zones of bank erosion. Analytical hierarchy process (AHP) was used to find the sensitive areas of the bank erosion for land management by weighted sum of different parameters. The suitability site map was classified into low, moderate, and high erosion zone. This map would help implement some preventive measures to mitigate the bank erosion within the Dibru River Basin.